Pembagian Harta Gono-Gini yang Berkeadilan Gender di Indonesia - Fiantika Armanda; Salsa Luthfiah Rezki; Kurniati Kurniati (Pusat Riset dan Inovasi Nasional, 2025)
The gender-equitable distribution of gono-gini property in Indonesia still faces challenges even though the principle of equality has been regulated in the Compilation of Islamic Law (KHI) and the Marriage Law. The principle of gender justice in Islamic law is rooted in sharia values that emphasize balance, benefits, and equality between men and women in acquiring and managing family property. However, practice in the field shows that there is a wrong understanding of society, patriarchal culture, and differences in judges' interpretations that often harm women. This research aims to analyze the form of distribution of gono-gini property according to Islamic law and national law, understand its implementation in the practice of religious justice, and formulate Islamic legal solutions that can realize a gender-fair distribution. The research method used is a literature review with a normative-qualitative approach through the study of primary, secondary, and tertiary legal materials. The results of the study show that the equitable distribution of gender is not only understood as a 50:50 division according to Article 97 of the KHI, but also includes recognition of economic and non-economic contributions, including the domestic role of the wife. Implementation in the religious courts still faces inconsistencies in judges' interpretations, low legal literacy, and socio-cultural barriers. The solutions offered by Islamic law include the application of the principles of shirkah, benefit, deliberation, and ijtihad of judges based on substantive justice.